Cytological examination of pleural cavity lavage accompanied by the study of gene promoter hypermethylation of p16 and O6-methylguanine-DNA-methyltransferase genes in diagnostics of non-small cell lung cancer metastatic changes into pleura - Kaczmarczyk, Grzegorz; Lewandowski, Roman; Trautsolt, Wanda; Ziółkowski, Adam; Kozielski, Jerzy (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: Metastases of non-small cell lung cancer (NSCLC) into pleura disqualify a patient from surgery and present a bad prognostic index. The aim of the study was to find out whether washing out the pleural cavity in such cases and examining obtained washings for presence of cancer cells will help to detect early NSCLC metastases into pleura, and also whether negative results of the cytology determine whether hypermethylation of these genes will increase the sensitivity of this examination. Material and methods : The study consisted of the examination of 76 patients, including 59 operated on for NSCLC and 17 operated on for other reasons. Pleural washing fluid collected during the surgery was subjected to cytological examination as well as examined to determine the presence of promoter region hypermethylation of p16 and MGMT genes. Results : Positive cytological results of pleural lavage were confirmed in 4 persons (7%) with NSCLC. The presence of promoter region hypermethylation of one or both examined genes was found in 3 patients (18%) in the control group and in 47 (80%) in the study group. Sex, occupational exposure, smoking cigarettes, and NSCLC histological type did not have an influence on the presence of cancer cells or hypermethylation in the pleural lavage fluid. Positive cytology results were more frequent at the T4 stage of NSCLC. Hypermethylation was more frequent in the research group (p < 0.01). Cancer cells and hypermethylation did not occur more frequently in pleural lavage fluid of patients with metastases into pleura. Conclusions : The cytological examination and promoter region hypermethylation assessment of the p16 gene and MGMT gene in pleural lavage cells do not allow one to detect early metastasis of NSCLC into pleura.